Housing Tenure Choice of Low-Income Household in Jabodetabek - Djoni Hartono; Reza A Budiman; Sasmita H Hastuti (Economics Development Analysis Journal, 2020)
This study aims to identify the preferences of low-income people in making housing tenure choices within the next 5 years. Each person has the right to have a place to live in. However, the options available for low-income people to own a home are limited. Therefore, information on the preferences of low-income people in purchasing houses needs to be identified so that the government can formulate effective and efficient intervention policies. A sample of 1030 samples was obtained using the stratification sampling method, of which 638 are households had rental status (taking households with the lowest level of welfare between 10-40%) in the Regency and City. Discrete choice models were used to determine the preferences in owning a home. The study revealed that demographic variables and household characteristics variables (household size and length of stay) had consistent negative relationships with preferences for buying a house in the future. Also, the government needs to take action so that the socialization of housing policy becomes more optimal, effective and targeted. The goal of the policy socialization should be directed to newly married couples.